ASSOCIATION BETWEEN AEROSOLS AND HOSPITALIZATIONS FOR RESPIRATORY DISEASES (ASSOCIAÇÃO ENTRE AEROSSÓIS E INTERNAÇÕES POR DOENÇAS RESPIRATÓRIAS) - Souza, Amaury de (Revista Brasileira de Climatologia, 2016)
The fires in Campo Grande have been a serious environmental problem. The objective is to study the trend of respiratory diseases (DAR), and correlates them with precipitation, wind speed, relative humidity, temperature, concentration of surface ozone, optical depth, number of outbreaks of fires and carbon monoxide. The records were obtained from the DAR Datasus; the outbreaks of fires and optical depth were obtained from the National Institute for Space Research and the concentration of ozone and carbon monoxide at the Institute of Physics of the UFMS. The mathematical correlation between the number of admissions for respiratory diseases and climatic indicators , indicated that the main source in order of significance are ozone, carbon monoxide, optical depth , fire outbreaks , wind speed , relative humidity , minimum temperature , rainfall . had two first principal components explained 91.48 % of the variance in the data studied, with a positive correlation between respiratory diseases, ozone, carbon monoxide, wind speed, optical depth and focus of fire and a negative correlation between rainfall, humidity and minimum air temperature, and the equation was determined with an error between the observed and estimated values of 2.29% and R- Sq = 89.1%.